EXTREMOPHILES: MICROORGANISMS WITH SOURCE OF BIOACTIVE COMPOUNDS AND POTENTIAL THERAPEUTIC POTENTIAL - E. Georgieva; V. Ivanov; G. Nikolova; K. Parlapanska; Y. Karamalakova (Trakia Journal of Sciences)
PURPOSE: The extremophile group of microorganisms that has the ability to live in extreme conditions. These microbes have made beneficial adaptations in their genetic and metabolic makeup to survive the hostile environment. Extremophiles possess unique genes and know how to breed in extreme conditions. These characteristics make extremophiles unique and are now widely used to produce important biomolecules that are stable at high or low temperature, extreme pH values, and even in the presence of lethal pollutants. This chapter seeks to evaluate and provide sufficient evidence for the antioxidant and protective capabilities of the novel bacterial metabolites Semiquinone glucoside derivative and N-acetyl tryptophan glucoside as a microbial species isolated from Bacillus sp. INM-1 fermented broth and their possible therapeutic action.